Evaluating erosion control performance of crimped straw mulch in comparison with RECPs on simulated highway roadsides. Issue 3 (July 2014) - Li, Ming-Han
Abstract : The objective of this study is to compare the crimped straw mulch with commercial, manufactured products on erosion control performance of (1) sediment loss and (2) vegetation establishment. Artificial rainfall was used to evaluate erosion control materials on two different slopes (2H:1V and 3H:1V). Two soil types (clay and sand) were tested. Four weight applications (2⋅24, 4⋅49, 6⋅73, and 8⋅98 metric tons ha −1 ) of crimped straw mulch were tested; and the vegetation establishment was tested on small greenhouse trays. The results show that sediment loss decreased with increasing weight of crimped straw mulch. On 3H:1V slopes, all rates of the crimped straw mulch could protect the soil surface either equal to or better than the proprietary products. For 2H:1V slopes, heavier applications of crimped straw mulch were able to reach the protection level of a manufactured product. Vegetation density testing yielded inconsistent results with no clear trend, which is likely because of the small test trays, the lack of replications, and the insufficient time for vegetation establishment.